La expresión plástica y su incidencia en el desarrollo del lenguaje oral, de los niños y niñas del primer año de educación general básica de la escuela fiscal mixta América y España, de la ciudad de Quito. Periodo lectivo 2013 - 2014 - Fonseca Iza, Aida Piedad (2014)
The research topic was: PLASTIC EXPRESSION AND ITS IMPACT ON THE BASIC GENERAL EDUCATION FIRST YEAR CHILDREN OF ORAL LANGUAGE DEVELOPMENT, OF ESPAÑA SCHOOL OF QUITO CITY. PERIOD 2013-2014. The General objective was: Educate parents and teachers as the Plastic or Art Techniques affects the Basic General Education First year Children of Oral Language Development, of España school of Quito city. Period 2013-2014. The methodologies used were: Scientist, Hypothetical Deductive and Statistical Model; The techniques that were applied were: Survey applied to teachers for the use of Visual Techniques in daily work, they do with the children of the España school; y , The Observing Guide to determine the of children Oral Language Development. The results were: 100% of teachers believe it is important to use the plastic techniques in daily work, considering to be able to fully exploit in the development process; and 70 % of children have an Oral Language Development Highly Satisfactory, 25% and 5% Satisfactory Unsatisfactory; therefore show that the vast majority of children have reached a level of development of oral language, as a result of work done by teachers ranging from pre related activities based on the Visual Techniques.